1976
DOI: 10.1038/sc.1976.8
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis in acute spinal cord injury: a comparison of 125I fibrinogen leg scanning, impedance plethysmography and venography

Abstract: Abstract. Twenty acute spinal cord injury patients were surveyed for deep venous thrombosis (DVT) by 1251 fibrinogen leg scanning, impedance plethysmography (IPG), and venography. Leg scanning was a more sensitive indicator of thrombotic events than IPG or venography. IPG was a reliable indicator of accumulated thrombosis. The incidence of DVT assessed by leg scanning alone was 100 per cent. Its occurrence as determined by either of the screening techniques was found to be considerably greater than those of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…There is evidence the range of motion is effective. An older survey for DVT by Todd et al 41 in acute SCI subjects without the now standard a range of motion to the extremities, revealed a high prevalence of DVT; but a later survey in the same setting with range of motion three times daily revealed a marked reduction in DVT, Table 2. 42 Nevertheless, a risk to this prophylaxis can be noted: at least five PE events and two fatal PE events immediately after range of motion or turns in bed in the acute SCI population have been reported.…”
Section: Diagnosismentioning
confidence: 99%
“…There is evidence the range of motion is effective. An older survey for DVT by Todd et al 41 in acute SCI subjects without the now standard a range of motion to the extremities, revealed a high prevalence of DVT; but a later survey in the same setting with range of motion three times daily revealed a marked reduction in DVT, Table 2. 42 Nevertheless, a risk to this prophylaxis can be noted: at least five PE events and two fatal PE events immediately after range of motion or turns in bed in the acute SCI population have been reported.…”
Section: Diagnosismentioning
confidence: 99%
“…Others have been using platelet aggregation inhibitors from the start, or as a relay (Hachen, 1978), and recently Charnley (1978) has given his experience concerning Hydroxochloroquine (Plaquenil ®) to prevent platelet adhesiveness and aggregation in hip surgery. Different laboratory investigation methods on DVT have been discussed in the literature, such as the 1251 Fibrinogen uptake tests, ultra-sound flow detection, venous occlusion plethysmography, phlebography (Todd et al, 1976), and have shown that the SCI patient is at a high risk. Hachen (1974) has given in his article all the aspects concerning biological action of different anticoagulants and their biological control.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of DVT in SCI patients during the first several weeks has varied from 14 per cent by clinical and radiological diagnosis (Philipps, 1963), 61 per cent using impedance plethysmography and contrast venography (Todd et at., 1976), to 100 per cent as determined by 1 2 51 fibrinogen uptake (Todd et at., 1976). Pulmonary embolism (PE) is a major cause of death for a few weeks after acute SCI.…”
Section: Introductionmentioning
confidence: 99%